12-6(5x-8)-9x=-2(-8x+7)-10

Simple and best practice solution for 12-6(5x-8)-9x=-2(-8x+7)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-6(5x-8)-9x=-2(-8x+7)-10 equation:


Simplifying
12 + -6(5x + -8) + -9x = -2(-8x + 7) + -10

Reorder the terms:
12 + -6(-8 + 5x) + -9x = -2(-8x + 7) + -10
12 + (-8 * -6 + 5x * -6) + -9x = -2(-8x + 7) + -10
12 + (48 + -30x) + -9x = -2(-8x + 7) + -10

Combine like terms: 12 + 48 = 60
60 + -30x + -9x = -2(-8x + 7) + -10

Combine like terms: -30x + -9x = -39x
60 + -39x = -2(-8x + 7) + -10

Reorder the terms:
60 + -39x = -2(7 + -8x) + -10
60 + -39x = (7 * -2 + -8x * -2) + -10
60 + -39x = (-14 + 16x) + -10

Reorder the terms:
60 + -39x = -14 + -10 + 16x

Combine like terms: -14 + -10 = -24
60 + -39x = -24 + 16x

Solving
60 + -39x = -24 + 16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-16x' to each side of the equation.
60 + -39x + -16x = -24 + 16x + -16x

Combine like terms: -39x + -16x = -55x
60 + -55x = -24 + 16x + -16x

Combine like terms: 16x + -16x = 0
60 + -55x = -24 + 0
60 + -55x = -24

Add '-60' to each side of the equation.
60 + -60 + -55x = -24 + -60

Combine like terms: 60 + -60 = 0
0 + -55x = -24 + -60
-55x = -24 + -60

Combine like terms: -24 + -60 = -84
-55x = -84

Divide each side by '-55'.
x = 1.527272727

Simplifying
x = 1.527272727

See similar equations:

| 15+45x=240 | | (c+4)(c-7)=0 | | 6x-10=8x-24 | | 3X+2+38=7X | | 12x-4=-32 | | 6x+9y=-27 | | x^6-7x^3= | | 6q-3p=p+q | | y/8=y/5-4/5 | | 6=-5x+7 | | 3x+-y=22 | | 2x+20-y= | | x^8-y^8= | | 34-y=y+6 | | 129x^4+33ax^2+9a= | | x^(7/2)=51,4 | | 3(6+5x)=18 | | -3(3p+2)-2(5-8p)=3(7+2p) | | 4x-(-3)(-2)=18 | | 4x-16=3x-1.9 | | 4x(-3)(-2)=18 | | 2(6+x)=32 | | -12h-2(2h-6)=-36 | | 3y^4+6y^3+3y^2=0 | | c-62=812 | | 5xy-10x= | | 9x^4+9x^3y-x^2-xy= | | 7m=147 | | 11-(k+3k)=43 | | 1/3,1/4,1/5,1/6= | | 2y-1/3=x | | 42=5v+2 |

Equations solver categories